Psychopharmacological characterization of effects of Ferula asafoetida linn. formulation in mouse on a Y-maze, EPM, and open field apparatus - Narayanan, Ramanujam; Gilbert, Bindu; Ravichandran, Santoshini; Bhuvaneswari, K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Asafoetida is an herbal food supplement that has numerous peripheral pharmacological actions. Its central nervous system effects have not yet been completely elucidated in both animals and human participants. The study focuses on deciphering the effects of this Herbaceutical with that of Donepezil and vitamin C in mouse models of short term novelty object recognition memory and open field test. Methods: The study was conducted in two stages - a pilot stage which assessed the most effective dose of asafoetida on cognition, followed by a post-pilot study phase wherein its effects at that dose were compared with those of Donepezil and vitamin C. Novelty Preference Test (NPT) on y-maze and Open field test on Open field box were used to evaluate the effects of the formulation on memory and motor activity in mice. Results: A dose of 400mg/day of asafoetida orally was found to improve memory significantly in comparison to 200mg/day in mice. Asafoetida showed a greater potency in improving memory than Donepezil and vitamin C. After 11 days of daily treatment with Asafoetida commercial powder, more than fifty percent of the mice showed an increase in recognition index of 0.7-0.8 as compared to 0.55 at baseline. Conclusions: Asafoetida powder has nootropic efficacy in mouse model - this has to be explored mechanistically and pharmaceutically to enable the psychopharmacological characterization of the active principles and its pharmacological effects in the central nervous system.